Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the given system of linear equations, we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Let's start by writing the system of equations clearly:
1. [tex]\[\frac{1}{3} x - \frac{1}{2} y = 4\][/tex]
2. [tex]\[5x - y = -5\][/tex]
### Step-by-Step Solution
Step 1: Eliminate fractions in Equation 1
Multiply both sides of Equation 1 by 6 to eliminate the fractions:
[tex]\[6 \left(\frac{1}{3} x - \frac{1}{2} y \right) = 6 \cdot 4\][/tex]
This simplifies to:
[tex]\[ 2x - 3y = 24 \][/tex]
So, the system of equations becomes:
1. [tex]\( 2x - 3y = 24 \)[/tex]
2. [tex]\( 5x - y = -5 \)[/tex]
Step 2: Solve for one variable
Let's solve for [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex] using Equation 2:
[tex]\[ 5x - y = -5 \][/tex]
Rearrange to solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5x + 5 \][/tex]
Step 3: Substitute y into Equation 1
Now substitute [tex]\( y = 5x + 5 \)[/tex] into Equation 1:
[tex]\[ 2x - 3(5x + 5) = 24 \][/tex]
Expand and simplify:
[tex]\[ 2x - 15x - 15 = 24 \][/tex]
[tex]\[ -13x - 15 = 24 \][/tex]
Add 15 to both sides:
[tex]\[ -13x = 39 \][/tex]
Divide by -13:
[tex]\[ x = -3 \][/tex]
Step 4: Solve for y using the value of x
Now that we have [tex]\( x = -3 \)[/tex], substitute this into [tex]\( y = 5x + 5 \)[/tex]:
[tex]\[ y = 5(-3) + 5 \][/tex]
[tex]\[ y = -15 + 5 \][/tex]
[tex]\[ y = -10 \][/tex]
Step 5: Write the solution
The solution to the system of equations is:
[tex]\[ x = -3 \][/tex]
[tex]\[ y = -10 \][/tex]
Therefore, the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations are [tex]\( \mathbf{x = -3} \)[/tex] and [tex]\( \mathbf{y = -10} \)[/tex].
1. [tex]\[\frac{1}{3} x - \frac{1}{2} y = 4\][/tex]
2. [tex]\[5x - y = -5\][/tex]
### Step-by-Step Solution
Step 1: Eliminate fractions in Equation 1
Multiply both sides of Equation 1 by 6 to eliminate the fractions:
[tex]\[6 \left(\frac{1}{3} x - \frac{1}{2} y \right) = 6 \cdot 4\][/tex]
This simplifies to:
[tex]\[ 2x - 3y = 24 \][/tex]
So, the system of equations becomes:
1. [tex]\( 2x - 3y = 24 \)[/tex]
2. [tex]\( 5x - y = -5 \)[/tex]
Step 2: Solve for one variable
Let's solve for [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex] using Equation 2:
[tex]\[ 5x - y = -5 \][/tex]
Rearrange to solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5x + 5 \][/tex]
Step 3: Substitute y into Equation 1
Now substitute [tex]\( y = 5x + 5 \)[/tex] into Equation 1:
[tex]\[ 2x - 3(5x + 5) = 24 \][/tex]
Expand and simplify:
[tex]\[ 2x - 15x - 15 = 24 \][/tex]
[tex]\[ -13x - 15 = 24 \][/tex]
Add 15 to both sides:
[tex]\[ -13x = 39 \][/tex]
Divide by -13:
[tex]\[ x = -3 \][/tex]
Step 4: Solve for y using the value of x
Now that we have [tex]\( x = -3 \)[/tex], substitute this into [tex]\( y = 5x + 5 \)[/tex]:
[tex]\[ y = 5(-3) + 5 \][/tex]
[tex]\[ y = -15 + 5 \][/tex]
[tex]\[ y = -10 \][/tex]
Step 5: Write the solution
The solution to the system of equations is:
[tex]\[ x = -3 \][/tex]
[tex]\[ y = -10 \][/tex]
Therefore, the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations are [tex]\( \mathbf{x = -3} \)[/tex] and [tex]\( \mathbf{y = -10} \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.